KEPASTIAN HUKUM TERHADAP JAMINAN MUTU PANGAN - Hasmauna Hasmauna; Basuki Rekso Wibowo (JOURNAL OF LAW AND NATION, 2023)
Food is one of the main aspects in fulfilling basic human needs which requires clarity and legal certainty regarding its quality and safety. This research aims to analyze legal certainty regarding food quality assurance with a focus on regulations and implementation in Indonesia. A qualitative approach was used by conducting literature studies and policy analysis related to food regulations in Indonesia. The research results show that regulations related to food quality in Indonesia have experienced significant developments, especially through Law Number 18 of 2012 concerning Food. However, consistent and effective implementation is still the main challenge faced in ensuring food safety for consumers. Even though there are responsible food control institutions, such as the Food and Drug Supervisory Agency (Badan POM), weaknesses are still found in supervision which tends to be inconsistent and less strict. Apart from that, the lack of cooperation between the government, the food industry and the community also makes it difficult to implement regulations properly. This research recommends the need to increase the capacity of supervisory institutions, stricter law enforcement against food quality violations, and increase public awareness of the importance of complying with food quality standards. Through these steps, it is hoped that legal certainty regarding food quality assurance in Indonesia can be improved, so that people can consume safe, healthy and quality food in accordance with established standards.